Dietary ecology of Chacma baboons (Papio Ursinus (Kerr, 1972) and Pleistocene Cercopithecoidea in Savanna environments of South Africa - Codron, Daryl Mark (Department of Geological Sciences, 2014)
Bibliography: leaves 124-140.